Estudo experimental e numérico da fluidodinâmica e das transferências de calor e massa em um leito de jorro contínuo: uso da técnica CFD - Rosa, Cezar Augusto da (2010)
In this work, the transport phenomena, which occur during the drying operation in a continuous spouted bed, are evaluated through experimental data and CFD simulations. Thus, this thesis was divided into three main parts: fluid dynamics, heat transfer and mass transfer. The fluid dynamics of a spouted bed, with continuous solids feeding, was studied through experimental data of static pressure, fountain height and air mass flow rate. A two-fluid two-dimensional model using the Euler-Euler approach was applied to simulate the fluid dynamics of the system. Gidaspow (1992) drag model was used to describe fluid-particle interface forces and the granular kinetic theory (Lun et al., 1984) to predict the solid phase stress. The commercial fluid dynamics code, FLUENT 6.3, was chosen to solve the model equations. The data obtained via CFD compared well with experimental results. In the heat transfer study, the conservation of energy equation was used, in conjunction with the fluid dynamics model, to simulate the heat transfer between the gas and particles in a continuous draft tube spouted bed. Two different Nusselt number correlations (Gunn, 1978; Kmiec, 1980) were used to calculate the heat transfer coefficient between the phases. The simulated results were compared with the experimental data obtained for the fluid temperature in the draft tube and annulus sections of the bed as well as for the solids outlet temperature. The drying simulations were done by coupling the transport phenomena, fluid dynamics, heat and mass transfer. An equation, based on thin layer drying data, was developed for the drying constant, which is a function of the fluid temperature and gas-solids relative velocity. The drying model presented physically consistent results and it seems to be promising for the drying analysis.